Jurisprudence rules: a critical study of definitions and differences - Al-Qasbawi, Radwan Muhammad (Journal of Islamic Sciences, 2022)
The objective of this study is to rationalize a part of the theoretical framework about the religious jurusprudence rules, and this is what relates to the contemporary productions in the field of defining the religious rules and differences between them and others. This study is meant to be critical celebrating the already done and pointing to the shortcomings in order to move to the practical side of theses rules, and pointing to their importance in simplifying the « Ijtihad », managing conflict,and legalizing legislation instead of repeating the theoretical paradigms every time.This research paper has adopted the critical system to approach this subject comparing, analysing and presenting observations in these axes:- Differentiating between the general and specific religious rules.- Selecting a definition for the religious rules based on an extensive study for the existing contemporary definitions.- Drawing attention to the differences between the old and contemporary researchers and between the religious rule and the rest.- Spot light on the differences so as to determine and systematize them.This study has come up with a bunch of results which are mainly:- The absence of a definition among the early or latest researchers has led to the expansion in the definitions of religious rules among contemporary investigators.- It is high time to exploit the abundance of definitions of religious rules to come up with one extensive definition which includes all the necessary elements and this is the intention of this research.- The main goal behind stressing the differences is to shy away any ambiguity between two similar sciences or concepts.- There was a lot of theoretical research done over the religious rule from definition, classification, grouping from all essential references to give a quality and mature product research.
Keywords: rules; religious; definitions; differences; criticism